2024
DOI: 10.3847/1538-4357/ad34ab
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Turbulent Fluctuations in the Sub-Alfvénic Solar Wind

G. P. Zank,
L.-L. Zhao,
L. Adhikari
et al.

Abstract: Parker Solar Probe (PSP) observed sub-Alfvénic solar wind intervals during encounters 8–14, and low-frequency magnetohydrodynamic (MHD) turbulence in these regions may differ from that in super-Alfvénic wind. We apply a new mode decomposition analysis to the sub-Alfvénic flow observed by PSP on 2021 April 28, identifying and characterizing entropy, magnetic islands, forward and backward Alfvén waves, including weakly/nonpropagating Alfvén vortices, forward and backward fast and slow magnetosonic (MS) modes. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Figure 7(c) shows the ratio of 2D and slab total turbulent-energy cascade rates ranging between 1 and 1.6. The 2D and slab cascade rates corresponding to E b and 〈u 2 〉 also exhibit solar cycle dependence as shown in Figure 7 Furthermore, the 2D magnetic energy density and turbulent kinetic energy cascade rates are consistently larger than the corresponding slab cascade rates throughout the solar cycle because the 2D turbulence contains more energy than slab turbulence (Zank & Matthaeus 1992;Bieber et al 1996;Zank et al 2017Zank et al , 2020Zank et al , 2024Adhikari et al 2017Adhikari et al , 2021bAdhikari et al , 2022. Figure 7(d) shows the ratio between 2D and slab cascade rates corresponding to the fluctuating kinetic energy and magnetic energy density.…”
Section: Tablementioning
confidence: 87%
See 1 more Smart Citation
“…Figure 7(c) shows the ratio of 2D and slab total turbulent-energy cascade rates ranging between 1 and 1.6. The 2D and slab cascade rates corresponding to E b and 〈u 2 〉 also exhibit solar cycle dependence as shown in Figure 7 Furthermore, the 2D magnetic energy density and turbulent kinetic energy cascade rates are consistently larger than the corresponding slab cascade rates throughout the solar cycle because the 2D turbulence contains more energy than slab turbulence (Zank & Matthaeus 1992;Bieber et al 1996;Zank et al 2017Zank et al , 2020Zank et al , 2024Adhikari et al 2017Adhikari et al , 2021bAdhikari et al , 2022. Figure 7(d) shows the ratio between 2D and slab cascade rates corresponding to the fluctuating kinetic energy and magnetic energy density.…”
Section: Tablementioning
confidence: 87%
“…Several studies (MacBride et al 2008;Adhikari et al 2022;Andrés et al 2022) found that the turbulent cascade rate in a direction perpendicular to the magnetic field is larger than that in parallel direction. This difference in the heating rate in both directions is likely to related the turbulence energy being larger in the perpendicular (or 2D) direction than in the parallel (or slab) direction (Zank & Matthaeus 1993;Bieber et al 1996;Adhikari et al Adhikari et al Adhikari et al Adhikari et al 2022;Zank et al 2017Zank et al , 2018aZank et al , 2024. We compute the 2D and slab cascade rates by using a method described by Adhikari et al (2022).…”
Section: Tablementioning
confidence: 99%
“…Nevertheless, these authors did suggest that solar wind density anisotropy varies with scale. On the other hand, Zank et al (2024) studied density fluctuations in sub-Alfvénic wind using mode-decomposition analysis, and found anisotropy dominated by a combination of the slablike entropy mode and the 2D-like backward propagating slow magnetosonic mode. The anisotropy of their entropy mode is consistent with our results, although their results extend over the scales = ´k 2 10 6 to -10 2 km 1 , which slightly overlaps with the smallest scales we investigate.…”
Section: Discussionmentioning
confidence: 99%
“…Energy could be supplied to the corona and solar wind via absorption of the energy contained in ion-sound or slow magnetosonic waves (e.g., Kellogg 2020, and references therein), that are often observed in the corona (e.g., DeForest & Gurman 1998; Wang et al 2009;Gupta et al 2012) and solar wind close to the Sun (Zank et al 2024). For q λ De = 1 (where λ De is the Debye length), the spectral energy density of parallel propagating ion-sound waves W q (erg cm −3 [cm −1 ] −3 ]) is related to the spectrum of density fluctuations S(q) ([cm −1 ] −3 ]) by (see, e.g., Appendix C in Lyubchyk et al 2017)…”
Section: Damping Of Ion-sound Wavesmentioning
confidence: 99%